(untitled) (Global Journal of Human-Social Science, 2025)
Introduction: The conducted research revealed the influence of the main aspects of the emotional and somatic state on the subjective well-being of patients with pain syndrome. An intrapersonal approach to understanding the subjectivity of the nature of pain experience will make it possible to individualize psychological rehabilitation in order to alleviate pain and improve the quality of life for patients. Purpose: Identification of intrapersonal factors that determine the subjective well-being of patients with pain syndrome. Materials and Methods: The results of a survey of 118 outpatients regarding their subjective well-being were analyzed. The analysis included an assessment of the subjective experience of pain (its intensity, sensory and emotional components), the level of alexithymia, the severity of psychosomatic complaints and emotional state. Used: Subjective Well-Being Scale (A. Perrudet-Badoux, G. Mendelsohn, J. Chiche, 1988, McGill Pain Questionnaire (MPQ, adapted by Kuzmenko V.V. et al., 1986), Toronto Alexithymia Scale (G.J. Taylor 1985 and the Giessen Subjective Complaints List (GBB) in the adaptation of the V.M. Bekhterev Institute), the Differential Emotions Scale (DES, K. Izard) was used to search for statistically significant factors influencing the level of subjective well-being of patients. analysis of variance (One-Way ANOVA). Results: Despite the fact that in the analyzed sample the level of alexithymia varies from 39 to 89 points (M = 65.65; SD = 11.20), (F (9, 109) = 6.38; p < 0.001), subjective wellbeing showed a tendency towards a directly proportional connection with deterioration of well-being and a statistically significant connection with almost all tested emotions according to the DES (indicated in the table), as well as with the coefficient of well-being (M = 1.62; SD = 0.54), (F (9, 109) = 6.73; p < 0.001). Conclusion: The main intrapersonal factors that determine the subjective well-being of patients suffering from pain have been sufficiently identified. The scientific substantiation of the subjective picture of pain will expand the tools for psychological diagnosis of such patients, taking into account their emotional state, painful affect and the presence of concomitant psychosomatic complaints in order to qualitatively improve rehabilitation measures.